Evaluation of Housing Quality in a Selected Urban Fringe of Ilorin, Kwara State, Nigeria (Sains Humanika, 2021)
Globally, a lot of research efforts have been put into investigating housing quality in urban areas, but little is known about housing situation in the urban fringes of developing nations. This article examines the factors influencing residents’ satisfaction with housing quality in Oke-Andi, an urban fringe in Kwara State, Nigeria. The research design for this study was quantitative in nature. Sampling was carried out at different stages during the field exercise. A preliminary survey of Oke-Andi in Ilorin through satellite imageries and reconnaissance revealed an approximate population of 593 buildings. From this, a 20% sample size, approximated to 120 buildings were randomly sampled and considered reasonable for the study. Using the housing quality criteria drawn from previous contextual studies, validated and pretested structured questionnaires were used to elicit data on respondents’ satisfaction with their dwelling unit, building unit, and neighbourhood quality. Information on residents’ socio-economic characteristics was also collected. From each selected building, a copy of the questionnaire was administered on the household heads or adult representatives. At the end of the survey, 120 questionnaires were administered, but only 100 were subsequently retrieved for data analysis. Simple frequency tables and Principal Component Analysis were used for the analysis of collected data. The result of PCA shows neighbourhood attributes, public utilities and building conditions as the factors influencing residents’ satisfaction with housing quality. The study recommends community driven urban renewal schemes for redevelopment, rehabilitation and upgrading of the quality of urban fringes.
Keywords: Residents’ satisfaction, neighbourhood characteristics, urbanization, housing quality, urban fringe.